CASH WAQF IN KELANTAN: PROSPECTS AND CHALLENGES - Siti Rohana Mohamad; Zunaidah Sulong (Journal of Islamic, Social, Economics and Development, 2022)
Cash waqf is an innovative instrument for Islamic Social Finance (ISF). It has thepotential to handle social concerns by supporting Muslims economy, education, welfare,religious issues, agriculture and social wellbeing. Cash waqf was introduced in Kelantan in2015 under MAIK as a contemporary waqf instruments that are beneficial to the Muslims inthe state. It increases the prospect of curbing poverty and a more structured socio-economicdevelopment in Kelantan. The objective of this paper is to look into the potential of cash waqfin dealing with the abovementioned issues, considering its flexibility and ease of collection.Besides that, this paper also attempts to address issues and challenges faced by the state ofKelantan in implementing cash waqf. They include lack of comprehensive legislation, lack oftransparency and accountable governance, and lack of regulatory or framework that ensureseffective collection and distribution.